Determinants of health seeking behavior for chronic non-communicable diseases and related out-of-pocket expenditure: results from a cross-sectional survey in northern Bangladesh - Binte Rasul, Fatema; Kalmus, Olivier; Sarker, Malabika; Adib, Hossain Ishrath; Hossain, Md Shahadath; Hasan, Md Zabir; Brenner, Stephan; Nazneen, Shaila; Islam, Muhammed Nazmul; De Allegri, Manuela (BMC, 2022)
This article was published in BMC [ © The Author(s). 2019 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/)] and the definite version is available at: https://doi.org/10.1186/s41043-019-0195-z. The Journal's website is at: https://jhpn.biomedcentral.com/articles/10.1186/s41043-019-0195-z#citeas